Common neuropsychological assessment measures as performance indicators in neuropsychological rehabilitation: An exploratory correlational study - Mendes,Liliana (2022)
ABSTRACT This study aims to identify neuropsychological assessment measures that can better guide the selection and difficulty level adjustment of neuropsychological rehabilitation tasks for patients with acquired brain injury. Eight patients with acquired brain injury were recruited from one rehabilitation institution. The neuropsychological protocol included standard neuropsychological tests targeting attention, memory, and executive functions. After the assessment, the patients enrolled in an intensive online cognitive neuropsychological rehabilitation training program (80 sessions of 49 cognitive training and 31 affective and psychosocial intervention sessions). The association between the assessment results and the training outcomes was measured to explore which measures were better associated with specific training outcomes. This study suggests that the results of specific conventionally administered neuropsychological tests can be good indicators of the patients’ performance in the cognitive training of attention and working memory. On the other hand, none of the tests provided valuable data regarding the patients’ ability to perform the executive functioning training tasks, perhaps because those appeal to everyday situations, which are not adequately represented in the administered tests. More research is needed, especially regarding the executive function.